2022
DOI: 10.1002/pi.6367
|View full text |Cite
|
Sign up to set email alerts
|

Itaconic‐acid‐based superabsorbent polymer with high gel strength and biocompatibility

Abstract: An elaborate surface-crosslinking method was introduced to enhance the low absorbency under load (AUL) and liquid permeability of itaconic-acid-based superabsorbent polymer (SAP). The effects of the surface-crosslinking reaction parameters of the absorption properties of the SAP were investigated. An increase in the content of distilled water and 1,4-butanediol used as the surface-crosslinking solution improved the AUL and liquid permeability of the SAP, whereas an increase in the distilled water content resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In addition to being a filler, it has been shown that coating with silicon dioxide in commercial epoxy resin has great importance in improving hydrogel performance, and incorporating silica nanoparticles was an exceptional technique for making polymer nanocomposites. Moreover, these are in the form of silanol groups and show strong reactivity toward the hydroxyl group of CMG, which contributes the most to the development of strength in superabsorbent products …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to being a filler, it has been shown that coating with silicon dioxide in commercial epoxy resin has great importance in improving hydrogel performance, and incorporating silica nanoparticles was an exceptional technique for making polymer nanocomposites. Moreover, these are in the form of silanol groups and show strong reactivity toward the hydroxyl group of CMG, which contributes the most to the development of strength in superabsorbent products …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these are in the form of silanol groups and show strong reactivity toward the hydroxyl group of CMG, which contributes the most to the development of strength in superabsorbent products. 38 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations